Exploring the Perceptions of EFL Learners on Ambiguity Tolerance: Sakarya University Sample - Orhan Kocaman; Melek Pamukoğlu (Sakarya University Journal of Education)
This study aims to investigate the perceptions of learners’ tolerance of ambiguity in the process of learning a foreign language. One of the language learning variables is ambiguity tolerance (AT) which can be defined as an attitude to understand the target structure with insufficient knowledge and to what extent learners tolerate the unknown items in the target language. Reacting the “ambiguous” structure shows whether a language learner is tolerant or intolerant; or to what extent learner tolerates the structure and how the feelings of the learners affect and shape their achievement on the degree of tolerance. A total of 109 students (43 preparatory class and 66 first-year) in English Language Teaching (ELT) department have responded to a 12-item questionnaire of Second Language Tolerance of Ambiguity Scale (SLTAS) which was modified by Erten and Topkaya (2009) for the purpose of shedding light on this issue. In order to highlight a more detailed perception, the scale was implemented on different levels of students to see their levels of avoiding ambiguity tolerance. The results indicated that students do not appear to tolerate ambiguous language structures well because of their high level of ambiguity tolerance. In addition, results have revealed that there is no significant difference between preparatory classes and first-year students’ levels of ambiguity tolerance. A open-ended questions consisting of four open-ended questions was carried out with six preparatory class and five first-year students with the aim of measuring the consistency between the statistical results and the results of the content analysis. The data obtained from the open-ended questions on tolerance of ambiguity revealed parallel results with some of the the studies reviewed in the current study.